Bohemian Bolsheviks After World War II: A Minority within a Minority - Wald, Alan (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2012)
Abstract Institutionalized forgetting about the scope of the Trotskyist experience in the United States was on display in every venue following the deaths of Peter Rafael Bloch (1921–2008), an authority on Puerto Rican artistic culture, and George Perle (born George Perlman, 1915–2009), a Pulitzer Prize-winning music theorist and composer once married to the sculptress and painter Laura Slobe (1909–58). Nothing written even hinted that the two iconoclasts were in the past highly educated and committed Marxists, or that revolutionary ideas oxygenated their cultural thinking at crucial moments.    Alarm over memory loss of this type is the motive for this present essay, which appraises the lives of Bloch, Perle, and Slobe along with other “Bohemians” who sought a vexed amalgam of unconstrained cultural creativity, personal freedom, and disciplined “Bolshevik” politics in the Socialist Workers Party (swp) during the late 1940s and 1950s.  What can be recovered of the political and personal passions of many “outlaw” lives on the Left, of cultural revolutionaries and sexual non-conformists, especially from those who infused anti-capitalism with anti-Stalinism, are only fragmentary narratives to be steered warily into coherency. For the postwar decade, one must write a kind of ghostly history, the reconstruction of the presence of an absence in a time of persecution.